2006
DOI: 10.1093/molehr/gal094
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-FISH analysis in a pericentric chromosome 1 inversion, 46,XY,inv(1)(p22q42), associated with infertility

Abstract: No phenotypic effect is observed in most inversion heterozygotes. However, reproductive risks may occur in the form of infertility, spontaneous abortions or chromosomally unbalanced children as a consequence of meiotic recombination between inverted and non-inverted chromosomes. An odd number of crossovers within the inverted segment results in gametes bearing recombinant chromosomes with a duplication of the region outside of the inversion segment of one arm and a deletion of the terminal segment of the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…This could partly explain the differences pointed out between the 2 species. Otherwise, in the case of very large inversions, it has been postulated [Anton et al, 2005;Chantot-Bastaraud et al, 2007] that synapsis of the inverted region with its homologous non-inverted segment prevails over pairing of the terminal segments, and that the regions outside the inversion may remain unpaired or aligned through heterosynapsis. This is consistent with the high proportions of recombinant gametes reported in the cases of In blue: data from the present study (inversions of chromosome 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could partly explain the differences pointed out between the 2 species. Otherwise, in the case of very large inversions, it has been postulated [Anton et al, 2005;Chantot-Bastaraud et al, 2007] that synapsis of the inverted region with its homologous non-inverted segment prevails over pairing of the terminal segments, and that the regions outside the inversion may remain unpaired or aligned through heterosynapsis. This is consistent with the high proportions of recombinant gametes reported in the cases of In blue: data from the present study (inversions of chromosome 1).…”
Section: Discussionmentioning
confidence: 99%
“…Although many cases of inversions have been described in man [Madan, 1995;Pettenati et al, 1995;Anton et al, 2005;Morel et al, 2007] as well as in pigs [Ducos et al, 2007], only few studies have reported on the analysis of chromosome segregation of pericentric [Anton et al, 2005;Malan et al, 2006;Chantot-Bastaraud et al, 2007;Morel et al, 2007;Caer et al, 2008] or paracentric [Devine et al, 2000;Anton et al, 2006;Bhatt et al, 2007Bhatt et al, , 2009Vialard et al, 2007] inversions. Fluorescent in situ hybridization on decondensed sperm nuclei (sperm FISH) using a combination of telomeric probes has become the state-of-the-art technique to assess the segregation patterns of inversions in man [Anton et al, 2007;Vialard et al, 2007;Caer et al, 2008].…”
mentioning
confidence: 99%
“…Centric breakage and fusion has been observed in Robertsonian translocation chromosomes of wheat and rye . Pericentric inversions in humans are often associated with decreased male fertility [Collodel et al, 2006;Chantot-Bastaraud et al, 2007, for review, see Anton et al, 2005, cancer [Mathew et al, 2002;Anelli et al, 2005;Pedrazzini et al, 2006], mental retardation [Ramadevi et al, 2002;Ulucan et al, 2006] and other diseases such as: [epilepsy: Grosso et al, 2004;cleft lip: Beiraghi et al, 2003; schizophrenia and learning disability: Hampson et al, 1999]. Such inversions may also be associated with duplications and deletions [López-Exposito et al, 2006;Patil and Phadke, 2007].…”
Section: The Centromerementioning
confidence: 99%
“…To date, few studies have analyzed the segregation products on the sperm nuclei using fluorescence in situ hybridization (FISH) in the case of pericentric inversion [Anton et al 2002;Anton et al 2006;Bernicot et al 2010;Caer et al 2008;Chantot-Bastaraud et al 2007;Malan et al 2006;Mikhaail-Philips et al 2004;Mikhaail-Philips et al 2005]. The frequency of the two abnormal gametes ((dup p/ del q and del p/dup q) was highly variable from 0% to 37.85%.…”
Section: Introductionmentioning
confidence: 99%